Frequency Of Depression In Patients With Diabetes Mellitus Type Ii From District Headquarter Hospital, Pakistan - Siddique, Irum; DOGAR, IMTIAZ AHMAD; MALIK, SALMA; HAIDER, NIGHAT; AFZAL, SAMREEN; CHEEMA, MOHSIN ALI; AZEEM, MUHAMMAD WAQAR (Journal of Pakistan Psychiatric Society, 2014)
Abstract